2014
DOI: 10.4161/15384101.2014.949501
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A type II-α regulatory subunit regulates the response of prostate cancer cells to taxane treatment

Abstract: In the last decade taxane-based therapy has emerged as a standard of care for hormone-refractory prostate cancer. Nevertheless, a significant fraction of tumors show no appreciable response to the treatment, while the others develop resistance and recur. Despite years of intense research, the mechanisms of taxane resistance in prostate cancer and other malignancies are poorly understood and remain a topic of intense investigation. We have used improved mutagenesis via random insertion of a strong promoter to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have shown that PRKAR2A deficiency predisposes patients to hematopoietic malignancies ( Saloustros et al, 2015 ). In addition, PRKAR2A has been found to regulate the response of cancer cells to chemotherapy, which might be the reason why our established model helped predict the curative effect of neoadjuvant therapy in TNBC patients ( Zynda et al, 2014 ). The thromboxane A2 receptor (TBXA2R) is a specific coordinator of the T prostanoid receptor (TPR), which is associated with the platelet activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PRKAR2A deficiency predisposes patients to hematopoietic malignancies ( Saloustros et al, 2015 ). In addition, PRKAR2A has been found to regulate the response of cancer cells to chemotherapy, which might be the reason why our established model helped predict the curative effect of neoadjuvant therapy in TNBC patients ( Zynda et al, 2014 ). The thromboxane A2 receptor (TBXA2R) is a specific coordinator of the T prostanoid receptor (TPR), which is associated with the platelet activity.…”
Section: Discussionmentioning
confidence: 99%
“…While germline and somatic mutations in the genes encoding the PKA R subunits have been characterized, little is known about the biological functions of aberrant PKA RIIα expression in human tumours [40]. Overexpression of PKA RIIα has been shown to increase the survival of prostate cancer cells treated with Taxol [41]. In HCC cells, anchoring of PKA RIIα at the Golgi is required for e cient and coordinated delivery of proteins and sphingolipids to the apical membrane [42].…”
Section: Discussionmentioning
confidence: 99%
“…Continuous production of cAMP can lead to activation of PKA dissociated by the PKA:AKAP inhibitor, releasing PKAc for substrate phosphorylation events in remote locations. The inadequate control of activity by regulatory subunit is seen in the PKArIIα overexpressing prostate cancer cells, in which application of PKI­(6–22) peptide further improved the cell survival . Considering that numerous AKAPs scaffold both AC and PKA, the application of ARCs emerge as a novel tool for studying the underlying mechanism of this important signaling pathway.…”
Section: Discussionmentioning
confidence: 99%